Paroxysmal atrioventricular block after heart transplantation in children: an early sign of rejection?. (14th October 2016) - Grutter, Giorgia; Alfieri, Sara; Calcagni, Giulio; Castelluzzo, Maria Assunta; Silvetti, Massimo Stefano; Parisi, Francesco; Drago, Fabrizio
Abstract: In OHT recipients, pathologic evaluation of the heart during acute rejection can show involvement of both the conduction system and the myocardium. We here describe the cases of a 9‐year‐old male with DCM and a 13‐year‐old female with RCM, who developed third‐degree PAVB associated with acute rejection 36 months and 24 months after OHT, respectively. We conclude that PAVB could be considered an early sign of acute rejection after OHT in children who exhibit post‐transplantation presyncope or syncope.